Social Development Management in the Period of Vietnam's Digital Transformation - Some Theoretical Issues - Manh Dung, Nguyen; Sinh Hung, Nguyen; Thi Thu Ha, Do (VNU Journal of Science: Policy and Management Studies, 2022)
Until the 13th Party Congress, the term/concept of "Social development management" has been increasingly perfected in terms of both content and policy and management implications. Nevertheless, the process of advocacy, development and practical manifestation of "development management" in Vietnamese social life is taking place rapidly. How does that process happen, especially in the context of national digital transformation? The relationship between social development management and digital transformation needs to be studied, supplemented and perfected from real life. From a macro perspective (considering national development orientations) and given document analysis (Party guidelines, State policies), the purpose of the article is to provide connotation of development management and social development in the new period (context of digital transformation ) in a wide range of aspects such as basic characteristics or content of the undertakings and policies. In doing so, it hopes to contribute to a better understanding of the term/concept of “social development management/governance". Keywords: Social development management, Digital transformation, New stage, Social development, Social management.